Transcriptome of the egg parasitoid Fopius arisanus: an important biocontrol tool for Tephritid fruit fly suppression. Issue 1 (December 2015) - Calla, Bernarda; Sim, Sheina; Hall, Brian; DeRego, Theodore; Liang, Guang; Geib, Scott
Abstract Background The Braconid waspFopius arisanus (Sonan) has been utilized for biological control of the Mediterranean fruit fly (Ceratitis capitata ), and the oriental fruit fly (Bactrocera dorsalis ), both of which are phytophagous fruit fly pests of economic importance in many tropical and subtropical regions of the world. We have sequenced and assembled the transcriptome of this wasp using tissue from four different life stages: larvae, pupae, adult males and adult females, with the aim to contribute foundational resources to aid in the understanding of the biology and behavior of this important parasitoid. Findings The transcriptome of the parasitic waspFopius arisanus was sequenced and reconstructed using a strategy that identified 15, 346 high confidence, non-redundant transcripts derived from 8, 307 predicted unigenes. In addition, Pfam domain annotations were detected in 78 % of these transcripts. The distribution of transcript length is comparable to that found in other hymenoptera genomes. Through orthology analysis, 7, 154 transcripts were identified as having orthologs in at least one of the four other hymenopteran parasitoid species examined. Approximately 4, 000 core orthologs were found to be shared betweenF. arisanus and all four of the other parasitoids. Conclusions Availability of high quality genomic data is fundamental for the improvement and advancement of research in any biological organism. Parasitic wasps are important in the biological control of agricultural pests. The transcriptome data presented here represent the first large-scale molecular resource for this species, or any closely related Opiine species. The assembly is available in NCBI for use by the scientific community, with supporting data available in GigaDB.